2018
DOI: 10.1108/ijius-09-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

UAV attitude estimation based on the dual filtering methods

Abstract: Purpose A toy UAV performs tumbling, rolling, racing and other complex activities. It is based on low-cost hardware and hence requires a better algorithm to estimate the attitudes more accurately with low power consumption. The proposed technique based on optimized Madgwick filter and moving average filter (MAF) ensures improved convergence speed in estimating the attitude, achieves higher accuracy and provides robustness and stability of the toy UAV. The paper aims to discuss this issue. Design/methodology/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Where some improvement opportunities are noted for attitude estimation such as, namely, unbounded steady state error, high density noise spectrum and sensitivity to external vibrations. Some of these issues were also mentioned in Zhuang et al (2018) and assessed through a sophisticated alternative estimation approach based on an optimized Madgwick filter and a MAF . It was shown that the algorithm reduces the estimation error in small vehicles with low-cost sensors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where some improvement opportunities are noted for attitude estimation such as, namely, unbounded steady state error, high density noise spectrum and sensitivity to external vibrations. Some of these issues were also mentioned in Zhuang et al (2018) and assessed through a sophisticated alternative estimation approach based on an optimized Madgwick filter and a MAF . It was shown that the algorithm reduces the estimation error in small vehicles with low-cost sensors.…”
Section: Introductionmentioning
confidence: 99%
“…A common estimation algorithm is the complementary filter, in which the accelerometer and gyroscope measurements of inertial measurement units ( IMU ) are combined. An issue with complementary filters is high frequency interference, which can be corrected through moving average filters ( MAF ) (Zhuang et al , 2018). Finally, quadrotor applications have appeared using low-cost IMUs .…”
Section: Introductionmentioning
confidence: 99%